Soldagem A-TIG em aço inoxidável ferrítico - Azevedo, Alessandra Gois Luciano de (2012)
The use of active flux in TIG process can be an alternative to increase the productivity since this technique increases the depth of penetration of weld bead maintaining the same parameters of conventional TIG welding. The results obtained indicate that the use of the traditional way of flux application tend to produce slag, which is hard to remove. In order to avoid this problem, are approach is by applying two flux strips alongside the joint, separated by a predetermined distance, defined as parameter \"a\". This technique is called Contraction Controlled Technique (CCT). The result with this methodology was satisfactory, allowing increasing the depth of penetration and ensuring a good weld bead surface finish. The objective of this research is to verify and analyze the influence of the use of Contraction Controlled Technique with the A-TIG process in the welding of ferritic stainless steel. It also aims to identify and quantify the main phenomena involved such as increase of the penetration, the changes in the arc, and changes in mechanical and metallurgical properties of the ferritic steel. For this purpose, it were done welding of ferritic stainless steels surfaces using the Contraction Controlled Technique, varying the width of the parameter \"a\", the distance between the piece and the electrode, the electrical current and welding speed. It was observed that the geometry of the weld beads has suffered modifications such as reduction in width and increased of the penetration of the weld beads for all cases where the active flux was used. The use of the active flux in TIG welding process is a technique that allows the increased of penetration depth of weld maintain keeping the same parameters used in the conventional TIG. However, it was not possible to increase the speed of the welding within the parameters used. When it was employed the technique of controlled contraction in a disalignment joint, the data showed that it is possible to improve results of arc direction, direct it to the edge of the board, using active flux and modifing both the parameter \"a\" and the deviation of the torch (dt). The application of this technique did not cause changes in the toughness or in the microstructure of the fusion zone the ferritic stainless steel.